Paradigm for a Riba-free Economy - Rodney Shakespeare; Sofyan Harahap; Talib Warsi (Indonesian Management and Accounting Research, 2011)
The world's political and economic tectonic plates are shifting. The old paradigm of mainstream neoclassical economics is collapsing. Paradigmatic revolution is in the air. But what form should paradigmatic revolution take? Western 'free market' finance capitalism is the main cause of present problems and so must be rejected: and also rejected is communism/socialism which abhors Allah, is politically oppressive, and is materially inefficient. The answer lies with genuinely independent nations which have economies free from fiba. These new economies will possess their own money supply and will not rely upon financial capital coming from abroad. Eschewing riba-interest (and interest-equivalents as in forms of Islamic banking), they will be based upon the use of national bank-issued interest-free loans which can be administered by the banking system (imposing only a charge for administration). These loans are for the development and spreading of productive (and associated consuming) capacity to every individual in society. The result is a proper balance of supply and demand (as is required by Say's Theorem) and a forwarding of social and economic justice. The new economics also founds new political, social and environmental solutions.